Opportunity in lost spaces: exploring the potential of edible landscapes in viaduct underpasses - Yang, Huihua; Hussein, Mohd Kher; Ibrahim,, Roziya; Zhuang, Qianda (Arts and Science Press, 2024)
This paper introduces the concept of edible landscapes to underutilized spaces in viaduct underpasses to explore their untapped potential. Using a case study approach that involves on-site observations, questionnaires, and photographic documentation, this study will document the characteristics of 29 space nodes beneath 18 viaducts and along their routes in Guangzhou’s Tianhe District. It analyzes user behavior and aspirations to activate the underutilized spaces of the viaduct underpass, optimizing their residual space, and enhancing their interactive potential. Furthermore, the paper proposes targeted design strategies for the rejuvenation and sustainable management of these underappreciated urban lost spaces. This study has two primary contributions. Firstly, it enhances the conceptual understanding of the lost spaces located in the viaduct underpass. Secondly, it investigates potential approaches and the benefits of utilizing these spaces for edible landscape development within the urban environment of Tianhe district in Guangzhou city. Keywords: viaduct underpass; edible landscape development; lost space